THE OSCE AND THE UKRAINE CRISIS: COOPERATION OVER CONFLICT - Stivani Ismawira Sinambela; Rafika Arsyad (Universitas Potensi Utama, 2023)
The role of the Organization for Security and Cooperation in Europe (OSCE) in handling cases in Eastern Ukraine in 2014 after Russia annexed the Crimea region. The annexation was followed by the outbreak of armed conflict between the pro-Russian separatist and the government side in the Eastern Ukrainian region. The OSCE played a strategic role in responding to the crisis. First, the OSCE is trying to mediate to defuse tensions between the two conflicting camps through comprehensive dialogue. Secondly, the OSCE sent a Special Monitoring Mission to monitor the dynamics of the crisis in Eastern Ukraine intensively. Third, the OSCE carries out a Minority Rights Assessment Mission to protect national minorities in Ukraine. Fourth, the OSCE also created the Interparliamentary Liaison Assembly through the Parliamentary Assembly organ to promote open and comprehensive dialogue to de-escalate regional conflicts. However, after nearly a decade of tensions in the Eastern Ukraine region, there was still no indication of any peace treaty negotiations; instead, the conflict expanded into a conflict between Russia and Ukraine. It can be considered that the OSCE has failed to mediate the crisis that occurred. The OSCE's strategy and mediation efforts in conflict resolution, combined with critical players' lack of political will, prevented a peaceful settlement. Far away, the United States' dominance of Ukraine hindered the peace process; this was in an attempt to maintain the status quo, ultimately benefiting the United States in maintaining its sphere of influence over Europe.